Genomewide analysis of microsatellite markers based on sequenced database in two anuran species - WEI, LI; SHAO, WEIWEI; MA, LI; LIN, ZHIHUA (Journal of genetics, 2020)
Eukaryotic and prokaryotic cell genomes exhibit multiple microsatellites. In this study, we characterized microsatellites in genomes and genes of Nanorana parkeri and Xenopus laevis. This characterization was used for gene ontology (GO) analysis of coding sequences (CDS). Compared to the genome of N. parkeri , the genome of X. laevis is larger and contains more number of microsatellites, but the diversity of both species are similar. Trinucleotide repeats in the genome of N. parkeri and dinucleotide and tetranucleotide repeats in the genome of X. laevis were the most diverse. In both the species, diversity of microsatellites was highest in intergenic regions, followed by intron and exon regions, and lowest in coding regions. Microsatellites in CDS are thus subject to higher selective pressure. Many microsatellites are concentrated upstream and downstream of genes in both species, suggesting suppression of repeats in the middle of protein–CDS. Repeats are enriched in regions near gene termini purely due to the biophysical constraints of protein structure. In GO analysis, two and five unique GO terms, only found in N. parkeri and X. laevis , respectively, indicate advantageous mutations during species evolution. Biological process, cellular component and molecular function ontology reflected in the GO analysis predicted that the microsatellites located in CDS can alter protein function and may provide a molecular basis for species adaptation to new and changing environments.